The Cambridge introduction to literature and philosophy - Cascardi, Anthony J., 1953- (Cambridge University Press, 2014)
Literature and philosophy have long shared an interest in questions of truth, value, and form. And yet, from ancient times to the present, they have often sharply diverged, both in their approach to these questions and in their relationship to one another. Moreover, the vast differences among individual writers, historical periods, and languages pose challenges for anyone wishing to understand the relationship between them. This Introduction provides a synthetic and original guide to this vast terrain. It uncovers the deep interests that literature and philosophy share while offering a lucid account of their differences. It sheds new light on many standing debates and offers students and scholars of literary criticism, literary theory, and philosophy a chance to think freshly about questions that have preoccupied the Western tradition from its very beginnings up until the present.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Literature -- Philosophy.; Philosophy in literature.; Truth in literature.; Values in literature.; Literary form.; Criticism.; Literature -- History and criticism -- Theory, etc.